2010
DOI: 10.1007/s12011-010-8829-4
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Cordyceps sinensis and Strontium in Prevention of Osteoporosis in Rats

Abstract: The effects of Cordyceps sinensis (Caterpillar fungus) and strontium ranelate on ovariectomized osteopenic rats was studied in this paper. After the rats were treated orally with C. sinensis, strontium, and C. sinensis rich in strontium ranelate (CSS) respectively, serum alkaline phosphatase (ALP), tartarate-resistant acid phosphatase (TRAP), serum osteocalcin (OC), homocysteine, C-terminal crosslinked telopeptides of collagen type I (CTX), estradiol, and interferon-gamma (IFN-γ) level were examined. The benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
(25 reference statements)
1
2
0
1
Order By: Relevance
“…In a rat ovariectomy model of estrogen deficiency, OVX caused significant increase in bone remodeling after 12 weeks of treatment. This finding agrees with those of other investigators [25, 26]. Furthermore, OVX significantly increased the level of RANKL and decreased the OPG level as well as the OPG/RANKL ratio in serum, demonstrating that the efficiency of ECH in OVX bone loss was mainly associated with the enhancing bone formation and inhibiting bone resorption probably through increasing the ratio of OPG/RANKL.…”
Section: Discussionsupporting
confidence: 93%
“…In a rat ovariectomy model of estrogen deficiency, OVX caused significant increase in bone remodeling after 12 weeks of treatment. This finding agrees with those of other investigators [25, 26]. Furthermore, OVX significantly increased the level of RANKL and decreased the OPG level as well as the OPG/RANKL ratio in serum, demonstrating that the efficiency of ECH in OVX bone loss was mainly associated with the enhancing bone formation and inhibiting bone resorption probably through increasing the ratio of OPG/RANKL.…”
Section: Discussionsupporting
confidence: 93%
“…C. sinensis rich in strontium ranelate reduced bone loss in experimental OVX osteopenic rats, in which a decrease in alkaline phosphatase (ALP) and tartrate-resistant acid phosphatase (TRAP) activities, a decrease in the interferon gamma (IFN-γ) level, and an increase in the osteocalcin (OC) and estradiol levels in plasma were observed [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…When ovariectomized rats were treated with cordyceps together with strontium, beneficial effects were obvious, such as improved bone mechanical strength and bone mineral content, and decreased urinary calcium excretion [89]. A follow-up study indicated that the combination treatment led to a decrease in alkaline phosphatase activity, TRAP activity, cross-linked telopeptides of collagen type I level, and interferon-γ level [90]. Using a rat model of disuse-induced bone loss and deterioration of trabecular microarchitecture, researchers have shown that an extract of C. sinensis exerted positive effects on improving the mechanical strength, bone mineral density and bone mineral content [91].…”
Section: Natural Products With Osteoprotective and Related Activitiesmentioning
confidence: 99%